Polygalae Radix: review of metabolites, pharmacological activities and toxicology - Liu, Meihua; Wang, Xin; Gao, Dejiang (Frontiers in Pharmacology, 2024)
Polygalae Radix is the dried root of Polygala tenuifolia Willd. or Polygala sibirica L., which has the effect of improving memory and cognitive function in traditional Chinese medicine. Modern pharmacological studies indicated that Polygalae Radix has rich pharmacological activities in vitro and in vivo, including protective effects on the nervous system, immune system, cardiovascular system and respiratory system, as well as antioxidant and antiepileptic pharmacological activities. Up to now, more than 160 metabolites from Polygalae Radix were identified, including triterpenoid saponins, xanthones, oligosaccharide esters and et al. The clinical practice of traditional Chinese medicine has proved that Polygalae Radix has a certain irritation to the throat, and a large or long-term use will stimulate the digestive tract, and the main toxic metabolite is saponins. Therefore, Polygalae Radix should be pr ocessed or used in combination with other Chinese herbal medicines to reduce the irritation to the throat and reduce gastrointestinal irritation. This article provides a review of the metabolites, pharmacological activity, and toxicology of Polygalae Radix. It also discusses the future research prospects and existing problems of Polygalae Radix, providing reference for further research on Polygalae Radix.